Mikhail Andreyevich Medvedev (to the 70th birthday) - article Editorial (Бюллетень сибирской медицины, 2005)
In 2005, Mikhail Andreyevich Medvedev, the honoured scientist of Russia, academician of RAMS, doctor of medical sciences, chief of normal physiology chair of the Siberian State Medical University, professor is 70. The biography of the outstanding scientist, main directions and achievements of his scientific, educational and social life are presented.